(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Josyp Romanovych Saldan began his working career as an ophthalmologist at the Mukolaiv Central Hospital in 1962, after graduating from Chernivtsi Medical Institute. In 1965, he entered the two-year post-graduate training program at the Filatov Institute, and underwent further post-graduate training at the institute in 1967 to 1969. After defending his Cand Sc (Med) thesis, The Diagnostic Value of Fluorescein Angiography and Ophthalmoscopy in Uveal and Retinal Inflammatory and Degenerative Disorders, in 1970, Dr. Saldan continued working for two years as a Junior Research Fellow at the institute. In 1972, he was sent to a business trip to Afghanistan, and worked as a consultant ophthalmologist at the Kabul Hospital for government employees until 1975. After coming back from Afghanistan in 1975, he continued working as a Junior Research Fellow, and, subsequently, as a Senior Research Fellow, at the Filatov institute, until 1988. Since 1988, he has been heading the Ocular Disease Department at the Pyrohov National Medical University, Vinnytsia, and was appointed as professor of the department in 2016. He defended his doctoral dissertation, Pathogenetic Features and Differential Approaches to Treatment of Early Simple vs Proliferative Diabetic Retinopathy, in 1990. Forty-six residents in ophthalmology and 345 junior ophthalmologists have been trained in the department under the leadership of Prof. Saldan. In addition, eight persons have earned a degree of Master of Medicine, and nine, a degree of Candidate of Medical Science.